Pengaruh Lingkungan Kerja, Pengembangan Karier, dan Persepsi Kerja terhadap Kepuasan Kerja dengan Burnout sebagai Pemediasi (Studi Kausal Pangkalan Sarana Operasi Bea dan Cukai) - Rahmad Efendi Sembiring; Ambarwati Ambarwati; Musa Alkadhim Alhabshy (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the direct and indirect effects of the work environment (X₁), career development (X₂), and work perception (X₃) on job satisfaction (Y), with burnout (Z) serving as a mediating variable. The topic is important because organizational improvements and increasing performance demands may unintentionally intensify psychological strain, particularly in high-risk and high-demand work settings. This research was conducted at the Customs and Excise Operational Facility Base, focusing on patrol boat crew members who face complex operational and emotional challenges. The study employed a quantitative explanatory research design to test causal relationships among variables. The sample consisted of 214 respondents drawn from a population of 458 patrol boat crew members. Primary data were collected through a structured questionnaire using a Likert scale. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), encompassing measurement model evaluation through convergent validity, discriminant validity, and reliability testing using composite reliability and Cronbach’s alpha. Structural model analysis included adjusted R², Q², variance inflation factor (VIF), effect size (F²), model fit, goodness of fit (GOF), and path coefficients, with statistical significance determined by T-statistics greater than 1.96 and p-values below 0.05. The results indicate that the work environment has a positive effect on burnout, while career development and work perception have negative and significant effects on burnout. Burnout negatively affects job satisfaction and fully mediates the relationship between the work environment and job satisfaction, while partially mediating the effects of career development and work perception. Work perception emerged as the strongest predictor of job satisfaction. These findings emphasize the crucial role of burnout as a psychological mechanism and highlight the paradox that modern work environments may increase emotional exhaustion if not balanced with adequate organizational support.